Effects of traditional vs. alternating whole-body strength training on squat performance - Ciccone, A. B.; Brown, L. E.; Coburn, J. W.; Galpin, A. J. (The Journal of Strength and Conditioning Research, 2014)
Traditional strength training with 80% of 1 repetition maximum (1RM) uses 2- to 5-minute rest periods between sets. These long rest periods minimize decreases in volume and intensity but result in long workouts. Performing upper-body exercises during lower-body rest intervals may decrease workout duration but may affect workout performance. Therefore, the purpose of this study was to compare the effects of traditional vs. alternating whole-body strength training on squat performance. Twenty male (24 ± 2 years) volunteers performed 2 workouts. The traditional set (TS) workout consisted of 4 sets of squats (SQ) at 80% of 1RM on a force plate with 3-minute rest between sets. The alternating set (AS) workout also consisted of 4 sets of SQ at 80% of 1RM but with bench press, and bench pull exercises performed between squat sets 1, 2 and 3 with between-exercise rest of 50 seconds, resulting in approximately 3-minute rest between squat sets. Sets 1-3 were performed for 4 repetitions, whereas set 4 was performed to concentric failure. Total number of completed repetitions of the fourth squat set to failure was recorded. Peak ground reaction force (GRF), peak power (PP), and average power (AP) of every squat repetition were recorded and averaged for each set. There was no significant interaction for GRF, PP, or AP. However, volume-equated AP was greater during the TS condition (989 ± 183) than the AS condition (937 ± 176). During the fourth squat set, the TS condition resulted in more repetitions to failure (7.5 ± 2.2) than the AS condition (6.5 ± 2.2). Therefore, individuals who aim to optimize squat AP should refrain from performing more than 3 ASs per exercise. Likewise, those who aim to maximize squat repetitions to failure should refrain from performing upper-body multijoint exercises during squat rest intervals.